How Does Important Sustainability Reporting for Investment Decision Making? - Sumiyati Sumiyati; Suhaidar Suhaidar (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
This study was conducted to examine the importance of sustainability reporting for investment decision making by prospective investors using belief-action-outcome (BAO) theory. This study is a rational investor behavior study in deciding the use of their assets by explaining it using Rational Decision Making Model (RDMM) theory. This study used an online quasi-experimental approach. The respondents of this research were prospective individual investors who understand the use of financial statements to make investments. This research was conducted with two tests. First, test the construct of variables. Second, test the subject's behavior with experiments. As for the experiments carried out two steps namely first, the subjects were given a questionnaire without any sustainability reporting. Second, subjects were given a questionnaire with instructions to read sustainability reporting first. The expected outcome is that investors tend to choose to buy shares of companies that also attach sustainability reports compared to companies without sustainability reports. Investors also tend to be rational in making decisions. This result showed the importance of sustainability report in rational decision making.